Increased Plasma Level of Longevity Protein Klotho as a Potential Indicator of Cognitive Function Preservation in Patients With Schizophrenia - Xiong, Jian-wen; Zhan, Jin-qiong; Luo, Tao; Chen, Hai-bo; Wan, Qi-gen; Wang, Yan; Wei, Bo; Yang, Yuan-jian (Frontiers in Neuroscience, 2020)
Cognitive impairments are a core feature of schizophrenia. Klotho is an anti-aging protein with demonstrated cognitive-enhancing effects on the brain. The purpose of this study was to investigate the differences in levels of plasma klotho between patients with schizophrenia and healthy controls, as well as the relationship between klotho level and cognitive function in patients. Forty patients with schizophrenia and 40 gender- and age-matched healthy individuals were recruited. Positive and Negative Syndrome Scale (PANSS) was used to assess the psychopathology of patients. A neuropsychological battery was performed to evaluate the cognitive function of participants. Plasma klotho was measured using enzyme-linked immunosorbent assay. We show that patients with schizophrenia performed worse in the neurocognitive tests than the healthy controls. The levels of plasma klotho were significantly higher in schizophrenia patients than in healthy controls (p < 0.001). In patients, plasma klotho levels were positively correlated with cognitive function with regard to attention (p = 0.010), working memory (p < 0.001), verbal memory (p = 0.044), executive function (p < 0.001), and composite cognitive score (p < 0.001). Stepwise linear regression analysis shows that executive function had the highest correlation with plasma klotho levels (β = 0.896, t = 8.290, p < 0.001). Collectively, these results indicate that anti-aging protein klotho may be implicated in the pathogenesis of schizophrenia, and increased klotho may act as a compensatory factor for the preservation of cognitive function in schizophrenia. Further studies are needed to investigate the dynamic changes of klotho and the mechanisms by which klotho modulates cognition in schizophrenia.